PENGARUH KOMPENSASI, KOMITMEN, KONFLIK, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI (Study Kasus Pada Badan Kepegawaian Daerah Kota Malang) - Mukhamad Amin Suryanulloh; Rois Arifin (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to determine and analyze the influence of compensation, commitment, conflict, and work environment on the performance of employees partially and simultaneously. This type of research is a quantitative research. Respondents in this study are employees in the Regional Personnel Board of Malang (BKD). The sample used in this study all employees who numbered 51 people. Data collection method used is to spread the questionnaire and interview. The results showed that compensation and conflict did not affect the performance of employees partially. While the commitment and work environment affect the performance of employees partially. Simultaneously the variable compensation, commitment, conflict, and work environment affect the performance of employees. Keywords: performance, compensation, commitment, conflict, work environment